Framing anticoagulation control according to clinical practice for patients with atrial fibrillation in Spain: a multidisciplinary vision trough AMFA Project - Cosín-Sales, Juan; Polo-García, Jose; Gavín Sebastián, Olga; Rubio Cabezas, Marta; Lloret Avellá, María (Frontiers in Cardiovascular Medicine, 2025)
Introduction and objectivesThe use of vitamin K antagonists (VKA) in patients with atrial fibrillation (AF) in Spain remains high, even though the available data on anticoagulation control (TRT, time in therapeutic range) shows suboptimal results. The objective of the AMFA project, an atlas of the management of anticoagulation in patients with AF, was to describe oral anticoagulation management in Spanish´ patients.Materials and methodsThe AMFA Project is a descriptive, multicenter study. It included information from 60 healthcare areas from each of the 17 Spanish regions. Consensus methodologies were used to analyze qualitative information obtained from the physicians' experience and perception and quantitative data collected through a specialized study questionnaire. In this questionnaire, experts were asked to include data of the last 10 consecutive patients attended with AF on anticoagulation treatment.ResultsRecords from 1,580 patients were obtained from 176 experts. Of them, 34.7% were cardiologists, 32.9% general practitioners (GPs), and 32.4% hematologists. The utilization rates of Direct Oral Anticoagulants (DOACs) and VKAs in clinical practice was 55.8% and 43.3%, respectively, which was not correlated with experts' perception. Clinical practice data revealed that 30.3% of the patients included did not have international normalized ratio (INR) or TTR data available, while only 3.8% of the experts reported that INR/TTR information was not available according to their perception. Considering only patients who had INR and TTR available, clinical practice showed that 59.0% of the patients had their coagulation in range, while the remaining 41.0% were uncontrolled. This result matches with the general perception reported by the experts, 62.6% of patients in range. Additionally, up to 22.2% of patients received DOAC treatment at suboptimal doses.ConclusionsThese data highlight the suboptimal control of the INR of patients, as well as the difficulties in DOACs access in Spain. The study uncovers the need to implement actions to improve INR control, facilitate access to DOACs treatment, and standardize AF patients' management. Establishing protocols that facilitate intervention may optimize the management of the patients with AF.